Dynamic Analysis of Thin Composite Cylindrical and Spherical Shells - Jebur, Qusai H. (Al-Khwarizmi Engineering Journal, 2018)
In this work, an investigation for the dynamic analysis of thin composite cylindrical and spherical shells is presented. The analytical solution is based upon the higher order shear deformation theory of elastic shells from which the developed equations are derived to deal with orthotropic layers. This will cover the determination of the fundamental natural frequencies and mode shapes for simply supported composites cylindrical and spherical shells. The analytical results obtained by using the derived equations were confirmed by the finite element technique using the well known Ansys package. The results have shown a good agreement with a maximum percentage of discrepancy, which gives a confidence of using this solution in prediction the dynamic analysis of cylindrical and spherical shells.